1994
DOI: 10.1111/j.1476-5381.1994.tb13141.x
|View full text |Cite
|
Sign up to set email alerts
|

Mepacrine‐induced inhibition of the inward current mediated by 5‐HT3 receptors in rat nodose ganglion neurones

Abstract: 1 With the whole-cell patch clamp technique, the effect of the antimalarial drug, mepacrine (quinacrine) on the inward current mediated by 5-HT3 receptors (5-hydroxytryptamine (5-HT)-induced current) was investigated in isolated nodose ganglion neurones of the rat. 2 5-HT and the selective 5-HT3 receptor agonists, 2-methyl-5-HT and m-chlorophenylbiguanide elicited an inward current which reversed at around 0 mV and quickly desensitized to a steady state level.3 Mepacrine dose-dependently inhibited the peak cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The inhibitory concentrations used in the bilayer studies (50 and 250 μM in this study) were higher than those used in patch‐clamp studies, particularly those that involved single‐channel recordings. The QC‐induced block of channel kinetics is voltage‐dependent for PrP(106–126) and in agreement with that reported for end‐plate currents (Adams and Feltz, 1980a, b) but unlike those of the 5‐hydroxytryptamine3 receptor‐induced inward current (Fan, 1994) and Ca 2+ channel currents (Mironov and Lux, 1992) in neurons. It is proposed that QC affects single‐ and whole‐cell currents by acting on open channels and modifying the desensitization kinetics (Spitzmaul et al, 2001) and by direct block of the channel (Nagano et al, 1996; Xiao et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The inhibitory concentrations used in the bilayer studies (50 and 250 μM in this study) were higher than those used in patch‐clamp studies, particularly those that involved single‐channel recordings. The QC‐induced block of channel kinetics is voltage‐dependent for PrP(106–126) and in agreement with that reported for end‐plate currents (Adams and Feltz, 1980a, b) but unlike those of the 5‐hydroxytryptamine3 receptor‐induced inward current (Fan, 1994) and Ca 2+ channel currents (Mironov and Lux, 1992) in neurons. It is proposed that QC affects single‐ and whole‐cell currents by acting on open channels and modifying the desensitization kinetics (Spitzmaul et al, 2001) and by direct block of the channel (Nagano et al, 1996; Xiao et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…The effects of QC (0.1–30 μM) have been examined on AChR channels in muscle (see Spitzmaul et al, 2001), L‐type Ca 2+ channels in cardiac membranes (Stokke et al, 1992; Nangano et al, 1996; Xiao et al, 2000) and neurons (Mironov and Lux, 1992), histamine‐induced K + currents in rat neurons (Fan, 1994), glibenclamide‐sensitive K + ; current in oocytes (Sakuta and Yoneda, 1994) and K + currents in neocortical neurons (Munakata et al, 2001). The effects on kinetics of single‐ and whole‐cell currents, recorded in both patch‐clamp and bilayer studies, were reversible generally for a QC concentration between 0.1–30 μM (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that other antidepressants such as imipramine, phenelzine, and iproniazid are able to inhibit the serotonergic current mediated by the 5-HT 3 receptor, blocking its action. This effect has not been elucidated so far, but 5-HT 3 receptor antagonism is constantly associated not only with gastroprotective activity, but also with antidepressant action [ 115 ].…”
Section: 5-ht 3 Receptorsmentioning
confidence: 99%